WRKY45 phosphorylation at threonine 266 acts negatively on WRKY45-dependent blast resistance in rice. (3rd August 2017) - Ueno, Yoshihisa; Matsushita, Akane; Inoue, Haruhiko; Yoshida, Riichiro; Jiang, Chang-Jie; Takatsuji, Hiroshi
ABSTRACT: WRKY45 is a central regulator of disease resistance mediated by salicylic acid signaling in rice and its activation involves phosphorylation by OsMPK6. OsMPK6 phosphorylates WRKY45 at Thr266, Ser294, and Ser299 in vitro . Phosphorylation of Ser294 and/or Ser299 is required for full activation of WRKY45, but the importance of Thr266 phosphorylation has remained unknown. Here, we report on the characterization of Thr266 phosphorylation of WRKY45 in rice. Transient expression of mutant WRKY45 revealed that Thr266 is phosphorylated in vivo, together with Ser294/299. Replacement of Thr266 by Asn did not affect the enhanced Magnaporthe oryzae resistance afforded by WRKY45 overexpression. By contrast, replacement by Asp negated the enhancement of M. oryzae resistance. These results suggest that Thr266 phosphorylation acts negatively on WRKY45-dependent disease resistance.